Immunohistochemical response in rats of beta-tricalcium phosphate (TCP) with or without BMP-2 in the production of collagen matrix critical defects - Luvizuto, Eloá Rodrigues [UNESP]; de Oliveira, Júlio César Silva [UNESP]; Gomes-Ferreira, Pedro Henrique Silva [UNESP]; Pereira, Cassiano Costa Silva [UNESP]; Faverani, Leonardo Perez [UNESP]; Antoniali, Cristina [UNESP]; Okamoto, Roberta [UNESP] (Elsevier, 2017)
This study aimed to assess the biological response of BMP-2 (bone morphogenetic protein-2) in supplementation with β-tricalcium phosphate (TCP) as a carrier in the bone healing of surgical defects in rats’ calvaria. A critical-size defect (5 mm in diameter) was filled with β-TCP alone or added with that plus 5 mg of BMP-2 at 5, 15, and 30 postoperative days. Histomorphometric and immunohistochemical (osteocalcin, collagen type I, and metalloproteinase-9) analysis was performed to assess the features of bone healing. Histological behavior and collagen type I labeling showed increased formation of the collagen matrix, leading to a higher percentage of newly formed bone and biomaterial for tissue and more total mineralization of pure TCP when compared to the other groups. The supplementation with BMP-2 promoted faster TCP remodeling; however, there was no statistically significant difference for the bone formed in both groups (P > 0.05). Collagen-matrix formation and new bone formation reached maximum levels when the defects were filled with pure TCP, even exceeding the levels from BMP-2 supplementation.
Keywords: BMP; Collagen matrix; Histologic evaluation; Immunohistochemistry